The impact of arts on prescription on individual health and wellbeing: a systematic review with meta-analysis - Jensen, Anita; Holt, Nicola; Honda, Sayaka; Bungay, Hilary (Frontiers in Public Health, 2024)
The evidence-base for the impact of participating in the arts for different aspects of health and wellbeing is growing. Arts on Prescription has gained increasing recognition as a method for fostering connections among individuals and communities, however, to date no systematic review of the impact on individual health and wellbeing has been conducted. This review aims to provide an understanding of individual health and wellbeing outcomes from participation in Arts on Prescription programmes. Methods: Major electronic databases were systematically searched,